The approach of moderation in Islam - Adnan Khmas, Omar (Opción, 2019)
Praise be to Allah, the Lord of the Worlds, and prayers and peace be upon the Most Merciful of the Messengers, our master Muhammad the faithful Prophet, and upon his family and companions, and after. After having entrusted to God and sought to clarify the matter, that Islam is a re- ligion of tolerance and compassion, came to humanity to be fair and remove from the misguided, chose the religion of values, which came by the Messenger of God Muhammad , where he says: (religion is pleased, But defeated him, they paid and approached). And the Quran urges us, where the Almighty says in his dear book: (religion is with God Islam). How much is this debt of many virtues, and great virtues, and great effects, and great secrets, urging the right minds and instinct to adhere to it and be literate, and guided by light, and the more sound mind, the yoke of insight intensified his attachment to this religion, And beautiful virtues. Islam is a religion that has reached the supreme end in its highness, the source of its strength of faith, truth, justice, sincerity, plains, ease, tolerance and sound mental thinking. For this I have resolved in my soul, if I am not lucky, to write in the method of moderation in Islam, and highlight the spirit, principles, objectives, and pillars, as this approach reflects the reality of Islam, and validity for all time and place. I say with all sincerity, after this long study, and the fair budget, if I were to choose the religion I believe in a firm belief in a firm belief in the heart. What I have chosen other than Islam is religion, for it is the religion of common sense, Religion of truth and peace, religion of solidarity and social solidarity, the religion of freedom and brotherhood and equality, the religion of compassion and mercy and humanity, the religion of forgiveness and pardon when ability, the religion of charity and altru- ism, the religion of God one Sunday, who says in his book: He also says: “Whoever wishes to convert to Islam is not a religion. He also says: “Today I have completed your religion and I have completed my grace and I have given you Islam as our reli- gion.” Today, my promise is fulfilled, and I have fulfilled my desire and faith, and I was in my heart of determination and sincerity, I offer you this humble research. In my research, I took into account scientific and practical accuracy, and was invoked in the mental ways of thinking, based on reason and logic to find the truth, and to reach the pure truth. Our Lord has entrusted you, and here is our repentance, and here is destiny.